Cardamonin induces autophagy and an antiproliferative effect through JNK activation in human colorectal carcinoma HCT116 cells. Issue 12 (15th June 2015) - Kim, Young-Joo; Kang, Ki Sung; Choi, Kyung-Chul; Ko, Hyeonseok
Graphical abstract: Abstract: Cardamonin (2′, 4′-dihydroxy-6′-methoxychalcone) is derived from Alpinia katsumadai Hayata (Zingiberaceae), a plant that has been used in Traditional Chinese Medicine for thousands of years. Several anticancer agents have been reported to induce autophagy, which either protects cells or further sensitizes cells to drug treatment. However, the possible autophagic and antiproliferative effects of cardamonin on the human colorectal carcinoma HCT116 cell line are unclear. In the present study, experiments were conducted to determine the effects of cardamonin on cell proliferation, cell cycle distribution, and stimulation of autophagy in cultures of the HCT116 cell line. The results showed that cardamonin inhibited cell proliferation, induced G2/M phase cell cycle arrest, and enhanced autophagy in HCT116 cells. We found evidence that cardamonin-induced autophagic and antiproliferative effects are regulated by the tumor protein p53. We also found that the enhanced activation of c-Jun N-terminal kinase (JNK) by cardamonin was partially regulated by p53 and was critical for cardamonin-induced autophagic and antiproliferative effects in HCT116 cells. These findings suggest that cardamonin or other anticancer agents that increase p53/JNK-dependent stimulation of autophagy could be used to effectively treat patients with colorectal carcinoma.